2021
DOI: 10.1021/jacs.1c00424
|View full text |Cite
|
Sign up to set email alerts
|

Auger-Assisted Electron Transfer between Adjacent Quantum Wells in Two-Dimensional Layered Perovskites

Abstract: Two-dimensional (2D) layered perovskites are naturally formed multiple quantum-well (QW) materials, holding great promise for applications in many optoelectronic devices. However, the further use of 2D layered perovskites in some devices is limited by the lack of QW-to-QW carrier transport/transfer due to the energy barrier formed by the insulating ligands between QWs. Herein, we report an Auger-assisted electron transfer between adjacent QWs in (C m H 2m+1 NH 3 ) 2 PbI 4 2D perovskites particularly with m = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…reported Auger‐assisted electron transfer in (C m H 2 m +1 NH 3 ) 2 PbI 4 2D perovskites with different alkyl chain lengths. [ 44 ] They found that for the m = 12 and 18 perovskite single crystals, the bandgap was approximately equal to the exciton binding energy, which leads to a strong coupling between excitons. An effective Auger recombination of an exciton causes the electrons in the other exciton to pass through the LUMO energy level of the ligand barrier and reach the adjacent QW to complete the charge transfer (Figure 3d).…”
Section: Structural Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…reported Auger‐assisted electron transfer in (C m H 2 m +1 NH 3 ) 2 PbI 4 2D perovskites with different alkyl chain lengths. [ 44 ] They found that for the m = 12 and 18 perovskite single crystals, the bandgap was approximately equal to the exciton binding energy, which leads to a strong coupling between excitons. An effective Auger recombination of an exciton causes the electrons in the other exciton to pass through the LUMO energy level of the ligand barrier and reach the adjacent QW to complete the charge transfer (Figure 3d).…”
Section: Structural Effectmentioning
confidence: 99%
“…Reproduced with permission. [44] Copyright 2021, American Chemical Society. demonstrated that as the thickness of the lead halide inorganic layer increases, the quantum confinement gets limited.…”
Section: Qwsmentioning
confidence: 99%
“…[241,242] In the meantime, there have been efforts to extract carriers from 2D perovskite quantum wells. [46,[243][244][245] One promising strategy to achieve efficient charge extraction out of 2D plane is adsorbing or attaching molecular acceptor/donor to perovskite surface. Li et al studied the interfacial charge transfer dynamics of colloidal CsPbBr 3 NPls at the presence of benzoquinone (BQ) or phenothiazine (PTZ).…”
Section: Transport Dynamicsmentioning
confidence: 99%
“…Besides, the mobility difference of QWs with varied layer thickness is also responsible for the confined charge transport behavior. 28,29 Although the gradient phase distribution has been reported to ensure the spontaneous charge transport across the 2D structure, a systematic crystal regulation method to optimize phase purity and distribution in this multiple QW structure is still absent. 30 Therefore, an in-depth understanding of the crystallization kinetics of 2D perovskites to regulate the crystalline orientation and QW structures is imperative to optimize the charge transport properties and break up the current efficiency barrier of the corresponding 2D PSCs.…”
Section: Introductionmentioning
confidence: 99%